Analisis Faktor-Faktor yang Mempengaruhi Literasi Keuangan Syariah pada UMKM di Kota Medan - Nasution, Hasbi Andika; Soemitra, Andri (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze financial literacy and determine the factors that influence the financial literacy of micro, small, and medium enterprises (MSMEs) in Medan City. This research uses a quantitative approach with a verification type of research. Primary data was obtained by distributing questionnaires to MSMEs in Medan City. The sampling technique uses proportional random sampling with a sample size of 100 respondents. Other data was obtained through observation and a literature study. The analysis technique used is multiple linear regression. The research results show that the financial literacy of MSME actors in Medan City is in the medium category. There are several factors that simultaneously influence financial literacy, namely age, level of formal education, and business income. Meanwhile, only the level of formal education and business income partially affect the level of financial literacy. Meanwhile, age has no effect on financial literacy. The authors recommend that future researchers study the influence of Sharia terms in UMKM to attract customer interest using more comprehensive methods, objects, and samples.